Fluoroscopy-guided shaped endobiliary biopsy at endoscopic retrograde cholangiography can accurately diagnose biliary neoplasia: Results from a large cohort - Wang, Bao-can; Wang, Kelly K.; Paul, Navin; Jayaraman, Vijay; Wang, Qiang; Abboud, Yazan; Jamil, Laith H.; Gaddam, Srinivas; Lo, Simon K. (Endoscopy International Open, 2021)
Background and study aims The sensitivity of using standard endobiliary forceps biopsy to diagnose neoplastic biliary lesions remains low. We have developed a unique biopsy approach, termed fluoroscopy-guided, shaped endobiliary biopsy (FSEB), in which the biopsy forceps are modified to improve diagnostic yield. In this study, we evaluate the diagnostic characteristics of FSEB for endobiliary lesions at endoscopic retrograde cholangiography (ERC).Patients and methods Consecutive patients undergoing FSEB between 1/2001 and 12/2014 were retrospectively enrolled. The identification of neoplastic lesions with FSEB, was the primary endpoint. The gold standard of neoplasia was histopathology, cytology or surgical histopathology. The benign cases were followed up for one year.Results A total of 204 patients undergoing 250 biopsy sessions by FSEB were analyzed. Per-patient analysis was performed and FSEB showed 81.1 % sensitivity and 88.2 % accuracy. FSEB detection of proximal biliary lesions was more sensitive (91.1 % vs 73.2 %, P < 0.01) and accurate (94.9 % vs 82.2 %, P < 0.01) compared to distal lesions. No complications from FSEB were reported.Conclusions FSEB shows high accuracy for diagnosis of neoplasia in biliary strictures, especially for proximal lesions. Future prospective randomized controlled studies are merited to further validate the role of FSEB as the first-line sampling tool for evaluation of biliary neoplasm.